The Implementation of Audio Visual Aid Media During Covid 19 Pandemic in Elementary School - Usman, Muhammad; Yusuf, Nidar (International Conference on Multidisciplinary Research, 2020)
Media are considered very important to meet the objectives to be achieved during the teaching and learning process. Media are used so that the students can enthusiastically participate in the learning process. However, due to the situation during this pandemic, all teaching and learning activities were carried out online. This research aims to determine students' interest in participating in the online way when given learning videos. This study used a pre-experimental quantitative method with one group pre-test post-test design. The results of this study have shown that there was an increase in the learning process when using learning videos. After giving the treatment, students eagerly want to know and were highly motivated in taking part in the learning process. Besidesm they were not bored when doing assignments given by the teacher. The increase in student learning that occurs is included in the moderate category, namely 0.42 based on the results of the normalized gain test (N-Gain). Based on the data analysis using a Gain test, the result is 0.41. The second class experienced an increase in participating in learning activities when given a learning video in the medium category. It is also said to be in the medium category because 0.7 g ≥ 0.3.  the, from the result of the questionnaire regarding the use of interesting and educational learning videos, the parents and students agreed to use instructional videos. It is because by using learning videos of sufficient time, students easily understand the material taught by the teacher. The conclusion obtained is that the application of using interesting instructional videos can increase children's interest in taking lessons during online learning. Keywords: Learning Media, Audio Visual Aid, Online Classes